GAMES AND PLAY: THE PLAYFUL AS MEDIATOR OF LEARNING IN PHYSICAL EDUCATION (Fiep Bulletin - online, 2011)
The objective of this research is to analyze the importance of play in the development of physical education classes, because this approach allows more diverse and creative classes, which provides a greater motivation and student participation, thereby its interest and learning. For this to happen it is important that teachers have the clear objective that aims to achieve by proposing certain physical activities for students. For this we used the literature search. It is crucial to offer challenging situations that motivate different solutions, stimulating creativity, discovery and rediscovery, as play activities allow an alliance between theory and practice. It is through play that children develop skills and different behavioral attitudes, builds knowledge and strengthening their self-confidence. For teachers who use the game as play activity that becomes a means for learning, and it is necessary to recognize some aspects of the students, their needs, interests, attitudes and conflicts so that way there through a game development all aspects of learning (cognitive, affective, moral, social and linguistic). For a better implementation of the game within the school context are needed to draw up clear goals and objectives, for without them this teaching strategy is doomed to fail or become just a filler between parallel activities. The recreational activities in schools can contribute to an improvement in the results of educators interested in promoting change. The study concluded that recreational activities would help to mediate and make the classroom a cheerful and friendly.
Keywords: Learning; Physical Education; Games